2014
DOI: 10.1021/jm500401x
|View full text |Cite
|
Sign up to set email alerts
|

Chasing Protons: How Isothermal Titration Calorimetry, Mutagenesis, and pKa Calculations Trace the Locus of Charge in Ligand Binding to a tRNA-Binding Enzyme

Abstract: Drug molecules should remain uncharged while traveling through the body and crossing membranes and should only adopt charged state upon protein binding, particularly if charge-assisted interactions can be established in deeply buried binding pockets. Such strategy requires careful pKa design and methods to elucidate whether and where protonation-state changes occur. We investigated the protonation inventory in a series of lin-benzoguanines binding to tRNA-guanine transglycosylase, showing pronounced buffer dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 54 publications
3
43
0
2
Order By: Relevance
“…The saltbridge type hydrogen bonds to Asp156 formed by the linbenzoguanines are replaced by weaker charge-assisted contacts in the lin-benzohypoxanthines. 9 Overall, in both ligand series, the parent lin-benzopurine scaffold is completely buried in the protein binding pocket and thus shielded from solvent access.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The saltbridge type hydrogen bonds to Asp156 formed by the linbenzoguanines are replaced by weaker charge-assisted contacts in the lin-benzohypoxanthines. 9 Overall, in both ligand series, the parent lin-benzopurine scaffold is completely buried in the protein binding pocket and thus shielded from solvent access.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The interaction pattern stabilizes the backbone flip and makes a dual ladder of parallel hydrogen bonds to the bound ligand possible, avoiding unfavorable secondary repulsive interactions among the closely approaching hydrogens in the hydrogen-bonding arrays. 9,19,20 Detailed analyses of the protonation inventory overlaid to the binding event showed that N(5) of the lin-benzoguanine scaffold becomes protonated, whereas N(3) remains in the neutral, uncharged state. 9 The lin-benzohypoxanthine scaffold adopts a very similar binding mode, and the interaction pattern to Asp156, Gln203, Gly230, Leu231, and Ala232 is analogously established.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations